2019
DOI: 10.1073/pnas.1818547116
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the interactions of calmodulin with GRK5 using a natural product chemical probe

Abstract: G protein-coupled receptor (GPCR) kinases (GRKs) are responsible for initiating desensitization of activated GPCRs. GRK5 is potently inhibited by the calcium-sensing protein calmodulin (CaM), which leads to nuclear translocation of GRK5 and promotion of cardiac hypertrophy. Herein, we report the architecture of the Ca2+·CaM–GRK5 complex determined by small-angle X-ray scattering and negative-stain electron microscopy. Ca2+·CaM binds primarily to the small lobe of the kinase domain of GRK5 near elements critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…To delineate the signaling mechanism(s) underlying stimulation of GRK5-mediated phosphorylation of the cardiac MR by the β 2 AR, we first examined the subcellular localization of the GRK5-MR interaction in H9c2 cardiac myocytes. Since both the MR and GRK5 can localize in both the cytoplasm and the nucleus [5,22,23], one important question arising from our present findings is which subcellular fraction these two proteins interact with each other in. To this end, we subjected H9c2 cell lysates to subcellular fractionation and we performed co-IP experiments in cytosolic and nuclear fraction extracts.…”
Section: Cardiac β 2 Ar-stimulated Grk5-mr Interaction Is Cytoplasmicmentioning
confidence: 83%
See 4 more Smart Citations
“…To delineate the signaling mechanism(s) underlying stimulation of GRK5-mediated phosphorylation of the cardiac MR by the β 2 AR, we first examined the subcellular localization of the GRK5-MR interaction in H9c2 cardiac myocytes. Since both the MR and GRK5 can localize in both the cytoplasm and the nucleus [5,22,23], one important question arising from our present findings is which subcellular fraction these two proteins interact with each other in. To this end, we subjected H9c2 cell lysates to subcellular fractionation and we performed co-IP experiments in cytosolic and nuclear fraction extracts.…”
Section: Cardiac β 2 Ar-stimulated Grk5-mr Interaction Is Cytoplasmicmentioning
confidence: 83%
“…In support of this, a recent study reported that protein kinase A (PKA), robustly activated by the cardiac β 1 AR, inhibits β 2 AR's ability to stimulate Ca 2+ -CaM signaling via ERKs and IP 3 in the caveolae of atrial myocytes [37]. It is thus quite plausible that the β 1 AR antagonizes the β 2 AR-induced, Ca 2+ -dependent GRK5 cytoplasmic/nuclear translocation in cardiac myocytes [22]. Of note, although it normally does not couple to G q proteins, the β 2 AR has been reported to directly activate PLCβ, eliciting intracellular IP 3 -dependent Ca 2+ mobilization/signaling [38].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations